The Difference of Using the Cooperative Approach Two Stay Two Stray and Jigsaw Type in Writing Skill of Drama Scripts at VIII Grade Students (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The aim of this research was to describe whether there is a significant difference or not in writing skill of drama scripts in grade VIII students of SMP Negeri 6 Padang, West Sumatra that were taught by using the Coperative Approach Two Stay Two Stray and Jigsaw type. The type of this research is a quantitative research with a quasi experiment method. This research uses the Non-equivalent Control Group Design. In this research, it was determined class VIII.2 as the experimental class I and VIII.6 as the experimental class II. The analyzing data is conducted by describing data. Then, it conducted data analysis requirements and hypothesis testing. The result is any significant difference in the writing skill of drama scripts at grade VIII students of SMP Negeri 6 Padang who were taught by the Cooperative Approaches Two Stay Two Stray and Jigsaw type. This is due to the similarity between the cooperative approaches in Two Stay Two Stray and Jigsaw type which students have the opportunity to explore information by asking questions and discussing with other groups. Thus, H0 is accepted and H1 is rejected because tcount<ttable = 0,19<1,67.